Śeksapiyaracyā rūpāntarāñcī dona parīkshaṇe - Apte, Hari Narayan, 1864-1919 (Mumbaī Marāṭhī Granthasaṅgrahālaya, 1979)
Critical articles on Marathi adaptation of the plays by William Shakespeare, 1564-1616.